Suppression of Defects Through Cation Substitution: A Strategic Approach to Improve the Performance of Kesterite Cu2ZnSn(S, Se)4 Solar Cells Under Indoor Light Conditions. Issue 4 (4th March 2021) - Park, Jongsung; Lee, Minwoo; Karade, Vijay; Shin, So Jeong; Yoo, Hyesun; Shim, Hongjae; Gour, Kuldeep Singh; Kim, Dongmyung; Hwang, Jiseon; Shin, Donghyeop; Seidel, Jan; Kim, Jong H.; et al.
Abstract : Recent efficiency advancements in kesterites have reinforced the use of Cu2 ZnSn(S, Se)4 (CZTSSe) in indoor photovoltaic applications. However, the performance of kesterites under low light intensity conditions is mainly hindered by deep‐level defects. In this study, a strategic approach of silver (Ag) and germanium (Ge) cation substitution to cure these defects are employed. The Ag‐doped CZTSSe (CZTSSe:Ag) and Ge‐doped (CZTSSe:Ge) samples experimentally demonstrated a significant improvement in kesterite device performance under all intensities of LED and white fluorescent lamp conditions are prepared. Interestingly, the CZTSSe:Ag device exhibited the highest performance levels, i.e., 1.2–1.5 and 2.5–3 times better than those of Ge‐doped CZTSSe:Ge and undoped CZTSSe, respectively. This improved device performance is mainly attributed to the reduced energy level of deep‐level defects in CZTSSe:Ag. Moreover, these defects assisted in the generation of a larger potential difference between the grain boundary and grain interior in the CZTSSe:Ag sample, attracting minority carriers near the grain boundary. Consequently, the improved carrier separation process reduced the carrier recombination losses and enhanced the power output under low light intensity conditions. This Ag and Ge cation substitution in kesterite is found to be an effective approach to improve the device performance under low light intensity conditions. Abstract : To improve the power output in indoor condition, a strategic and efficient approach of silver (Ag) and germanium (Ge) cation substitution is used to lessen these defects. The CZTSSe:Ag device exhibits the highest performance levels, better than those of Ge‐doped CZTSSe:Ge and undoped CZTSSe, respectively, under light‐emitting diode and white fluorescent lamp conditions.